Pengembangan Bussiness Model Canvas (BMC) pada usaha ekonomi kreatif kain sutera di Kabupaten Wajo: Sudi kasus pada UMKM Losari Silk - Mutmainnah, Ismiah; Ibrahim, Helda; Rahman, Syamsul (LP3M Universitas Putra Bangsa, 2025)
The silk industry in Wajo Regency carries significant historical and cultural value, yet its sustainability is challenged by limited raw materials, market competition, and underutilized local resources. This study analyzes the business model of Losari Silk using the Business Model Canvas (BMC) framework and explores opportunities for sustainable development. A qualitative descriptive approach was applied through observation and in-depth interviews with business owners and key partners. The results show that Losari Silk already has a solid business model, but further innovation is required, particularly in optimizing social media, improving raw material management, and expanding collaborations with government and private sectors. The findings also suggest that supportive policies are needed to strengthen entrepreneurial capacity through digital technology, wider partnerships, and better access to resources. Strengthened synergy among entrepreneurs, government, and private stakeholders is expected to create a sustainable business ecosystem, enhance competitiveness, preserve cultural heritage, and contribute to regional economic growth.